A pilot study on developing mucosal vaccine against alveolar echinococcosis (AE) using recombinant tetraspanin 3: Vaccine efficacy and immunology. - Zhisheng Dang; Kinpei Yagi; Yuzaburo Oku; Hirokazu Kouguchi; Kiichi Kajino; Jun Matsumoto; Ryo Nakao; Hiroyuki Wakaguri; Atsushi Toyoda; Hong Yin; Chihiro Sugimoto (Public Library of Science (PLoS), 2012)
BACKGROUND: We have previously evaluated the vaccine efficacies of seven tetraspanins of Echinococcus multilocularis (Em-TSP1-7) against alveolar echinococcosis (AE) by subcutaneous (s.c.) administration with Freund's adjuvant. Over 85% of liver cyst lesion number reductions (CLNR) were achieved by recombinant Em-TSP1 (rEm-TSP1) and -TSP3 (rEm-TSP3). However, to develop an efficient and safe human vaccine, the efficacy of TSP mucosal vaccines must be thoroughly evaluated. METHODOLOGY/PRINCIPAL FINDINGS: rEm-TSP1 and -TSP3 along with nontoxic CpG ODN (CpG oligodeoxynucleotides) adjuvant were intranasally (i.n.) immunized to BALB/c mice and their vaccine efficacies were evaluated by counting liver CLNR (experiment I). 37.1% (p < 0.05) and 62.1% (p < 0.001) of CLNR were achieved by these two proteins, respectively. To study the protection-associated immune responses induced by rEm-TSP3 via different immunization routes (i.n. administration with CpG or s.c. immunization with Freund's adjuvant), the systemic and mucosal antibody responses were detected by ELISA (experiment II). S.c. and i.n. administration of rEm-TSP3 achieved 81.9% (p < 0.001) and 62.8% (p < 0.01) CLNR in the liver, respectively. Both the immunization routes evoked strong serum IgG, IgG1 and IgG2α responses; i.n. immunization induced significantly higher IgA responses in nasal cavity and intestine compared with s.c. immunization (p < 0.001). Both immunization routes induced extremely strong liver IgA antibody responses (p < 0.001). The Th1 and Th2 cell responses were assessed by examining the IgG1/IgG2α ratio at two and three weeks post-immunization. S.c. immunization resulted in a reduction in the IgG1/IgG2α ratio (Th1 tendency), whereas i.n. immunization caused a shift from Th1 to Th2. Moreover, immunohistochemistry showed that Em-TSP1 and -TSP3 were extensively located on the surface of E. multilocularis cysts, protoscoleces and adult worms with additional expression of Em-TSP3 in the inner part of protoscoleces and oncospheres. CONCLUSIONS: Our study indicated that i.n. administration of rEm-TSP3 with CpG is able to induce both systemic and local immune responses and thus provides significant protection against AE.